Evaluation of risk factors for poor wound healing after cesarean delivery in patients with gestational diabetes mellitus: a retrospective study - Yan Liu; Ye Wang; Shao-Hua Gao; Hui Wu; Chun-Yu Zhang; Jia-Li Yao; Pei-Xia Cai (BMC Surgery)
Abstract Background Poor wound healing (PWH) are significant complications following cesarean deliveries, particularly in patients with gestational diabetes mellitus (GDM) due to hyperglycemia-induced immune dysfunction and impaired wound healing. Identifying specific risk factors is essential for developing effective preventive strategies and improving maternal outcomes. Methods This retrospective study, conducted from January 2020 to August 2023, followed STROBE guidelines. A total of 268 GDM patients who underwent cesarean delivery were included, with 5 lost to follow-up, yielding a 98.2% follow-up rate. Patients were divided into two groups: the PWH group (n = 26) and the control group (n = 242). Comprehensive data on maternal age, gestational age, pre-pregnancy BMI, IVF-ET use, uterine scarring, surgery type (emergency vs. elective), operative time, and infections (Candida albicans and Group B Streptococcus) were collected. Statistical analyses included Chi-square, Fisher’s exact tests, and multivariate logistic regression to identify independent risk factors for PWH. Results The overall incidence of PWH was 9.7%, with the majority being superficial infections, including suture reactions (38.5%), bleeding and exudation (30.8%), abscesses (15.4%), and fat liquefaction (11.5%). Deep infections were rare, with only 3.8% presenting as endometritis and no cases of pelvic abscess. Multivariate logistic regression identified the following significant independent risk factors for PWH: premature rupture of membranes (OR = 10.88, 95% CI: 1.70–71.25, P = 0.002), Candida infection (OR = 5.77, 95% CI: 1.89–18.65, P = 0.003), emergency cesarean delivery (OR = 2.32, 95% CI: 1.02–5.48, P = 0.047), a scarred uterus (OR = 3.68, 95% CI: 1.43–9.39, P = 0.006), and prolonged operative time (≥ 1 h; OR = 2.55, 95% CI: 1.02–3.73, P = 0.031). Conclusions Prolonged operative time, premature rupture of membranes (PROM), emergency cesarean delivery, and uterine scarring were identified as independent risk factors for PWH in GDM patients. Candida infection also showed a statistical association but was based on limited case numbers and should be interpreted cautiously. Targeted perioperative strategies may help reduce PWH risk in this population.